2004
DOI: 10.1103/physrevb.70.155313
|View full text |Cite
|
Sign up to set email alerts
|

Cd-vacancy andCd-interstitial complexes inSiandet al.

Abstract: The electrical-field gradient (EFG), measured, e.g., in perturbed angular correlation experiments, gives particularly useful information about the interaction of probe atoms like 111 In/ 111 Cd with other defects. The interpretation of the EFG is, however, a difficult task. This paper aims at understanding the interaction of Cd impurities with vacancies and interstitials in Si and Ge, which represents a controversial issue. We apply two complementary ab initio methods in the framework of density-functional the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
5
15
0
2
Order By: Relevance
“…2(b). Furthermore, ab initio calculations have shown that in the In-V, the Cd-V and the Cd-Ge I defects, the impurity prefers the BC site to the S site [16,17]. All of these results strongly point towards the fact that the In atoms observed on the BC site in our study are part of the In-V and/or In-Ge I defect complex.…”
Section: And 300supporting
confidence: 69%
See 1 more Smart Citation
“…2(b). Furthermore, ab initio calculations have shown that in the In-V, the Cd-V and the Cd-Ge I defects, the impurity prefers the BC site to the S site [16,17]. All of these results strongly point towards the fact that the In atoms observed on the BC site in our study are part of the In-V and/or In-Ge I defect complex.…”
Section: And 300supporting
confidence: 69%
“…In order to understand the structural configuration of simple defects such as the In-vacancy defect, ab initio density functional calculations were performed, resulting in In atoms occupying the bond-centered (BC) site [16]. The occupancy of the bond-centered site was calculated for many high-Z impurity atoms in the impurity-vacancy complexes, as well as for Cd in the Cd-self-interstitial defect complex [16,17]. Similar theoretical results have been found for the In-V defect in Si, where the In atom was found to occupy the BC site as well [16,18].…”
Section: In-dopedmentioning
confidence: 99%
“…32 A similar result was obtained in other systems such as Cd complexes in Si and Ge. 31 Based on these results spin-polarized calculations were performed. In the case of the charged cell (q = + 1) we did not find a magnetic solution, while in contrast, APW + lo predicts spin polarization for the case q = 0.…”
Section: B Zr 31 Tao 64mentioning
confidence: 99%
“…[24][25][26][27] From a theoretical point of view, it has been shown that point defects such as cation or oxygen vacancies or electron trapping at an impurity site can be the origin of the magnetism. [28][29][30][31] Very recently, a combination of hyperfine experiments [using time-differential perturbed angular correlations spectroscopy (TDPAC) with 181 Ta as a probe] and ab initio calculations has been applied to study the electronic structure of Ta-doped hafnium dioxide. 32 The study revealed that Ta introduces impurity levels in the band gap of semiconducting monoclinic HfO 2 (m-HfO 2 ), and induces significant structural distortions in the host lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have studied by density functional calculations the Cd-vacancy and Cd-interstitial complexes in Si and Ge 4 , aiming at understanding the electric field gradients (EFG) measured in perturbed angular correlation experiments for the 111 In/ 111 Cd probe atom. We find that both in Si and Ge the substitutional Cd-vacancy complex is instable and relaxes into the highly symmetrical Cd-split-vacancy complex, being about 1eV lower in energy than the substitutional configuration.…”
Section: Introductionmentioning
confidence: 99%